The significance of spatial length scales and solute segregation in strengthening rapid solidification microstructures of 316L stainless steel. (1st February 2020) - Pinomaa, Tatu; Lindroos, Matti; Walbrühl, Martin; Provatas, Nikolas; Laukkanen, Anssi
Graphical abstract: Abstract: Selective laser melting (SLM) can produce outstanding mechanical properties in 316L stainless steel. Nonetheless, the technique can lead to considerable variation in quality. This reflects an incomplete understanding and control of the process-structure-properties linkage. This paper demonstrates how length-scale informed micromechanical behavior can be linked to solidification microstructures and how these structures depend on SLM process conditions. This linkage is produced by sequential phase field and crystal plasticity simulations. Rapid solidification is described with a recent quantitative phase field model with solute trapping kinetics, where a range of process conditions are considered in terms of thermal gradients and pulling speeds. The predicted morphological transitions (dendritic-cellular-planar) are consistent with experiments, including segregation-free microstructures, which emerge in planar growth conditions. The predicted cell spacing vs. cooling rate data are also consistent with experiments. The simulated cellular structures produced through phase field modeling are then analyzed with a Cosserat crystal plasticity model with calibrated length-scale and hardening effects and with a solid solution strengthening description that depends on the local microsegregation. It is found that the length scale characteristics and solute segregation greatly influence the overall hardening behavior and affect plastic localization and the evolution of geometrically necessary dislocation (GND) type hardening. Our results suggest that the material strength of SLM 316L steel is more sensitive to cell spacing (microstructural length scale) than to the magnitude of solute segregation. Pulling speed (solidification velocity) is identified as the main process condition determining the material micromechanical behavior. Further analysis of idealized polycrystalline structures demonstrated that plastic incompatibilities and subgrain cell interactions with grain boundaries lead to notable strengthening. The presented sequential phase field-crystal plasticity modeling scheme is a proof-of-concept for systematically investigating and discovering new compositions, process conditions and microstructures for SLM.